Applying psycholinguistic principles to spelling and word learning - Leitao, Suze (2003)
This article presents a case study to illustrate the application of theory and research to intervention for a child with dyslexia and auditory processing disorder (APD).The use of the speech processing profile developed by Joy Stackhouse and Bill Wells provided a framework for psycholinguistic based intervention for spelling and word learning. Strategies for addressing lexical retrieval/storage difficulties, word learning and spelling within this framework are discussed.